2022
DOI: 10.1155/2022/9873777
|View full text |Cite|
|
Sign up to set email alerts
|

Image Segmentation Technology Based on Attention Mechanism and ENet

Abstract: With the development of today’s society, medical technology is becoming more and more important in people’s daily diagnosis and treatment and the number of computed tomography (CT) images and MRI images is also increasing. It is difficult to meet today’s needs for segmentation and recognition of medical images by manpower alone. Therefore, the use of computer technology for automatic segmentation has received extensive attention from researchers. We design a tooth CT image segmentation method combining attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…At the same time, the high-dimensional problem of hyperspectral remote sensing data will be further amplified in deep learning, so the high time consumption has become a bottleneck limiting the application of deep learning. Compressing the learning of inefficient samples by active learning [8], reducing the amount of learning parameters by distillation learning [9], and optimizing the calculation method of feature extraction layer by lightweight deep learning models (GhostNet, MobileViT, etc.) [10,11] can weaken this effect to a certain extent, but this is not the expected final solution.…”
Section: Research Backgroundmentioning
confidence: 99%
“…At the same time, the high-dimensional problem of hyperspectral remote sensing data will be further amplified in deep learning, so the high time consumption has become a bottleneck limiting the application of deep learning. Compressing the learning of inefficient samples by active learning [8], reducing the amount of learning parameters by distillation learning [9], and optimizing the calculation method of feature extraction layer by lightweight deep learning models (GhostNet, MobileViT, etc.) [10,11] can weaken this effect to a certain extent, but this is not the expected final solution.…”
Section: Research Backgroundmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%